HIGH⁃FIDELITY FINITE ELEMENT SIMULATION AND EXPERIMENTAL VERIFICATION OF BOLT PRELOAD FORCE UNDER TIGHTENING TORQUE - QIAN Jin; CHEN Guo; CUN WenYuan; ZHAO XuSheng; ZHANG Xu; ZHAO ZhengDa (Jixie qiangdu)
The finite element simulation method of bolt torsion under the tightening torque process was carried out,a quantitative relation between the tightening torque and the bolt preload was established for an actual structure.Firstly,the geometric model of the bolt with three⁃dimensional oblique thread was built,and the finite element mesh with thread was divided by using Hypermesh software,and the corresponding mechanical contact pairs were redefined.Then,Ansys Workbench software was used to apply the different sizes of tightening torque to the lower surface of the nut to obtain the magnitude of the corresponding axial force,so that the functional relation between the tightening torque and the bolt tension could be obtained.Finally,a bolt preload test was designed and the experimental,emulational and theoretical results were compared to verify the method.The results show that the results of the finite element simulation model are closer to the experimental results compared to the theoretical calculation results.The high⁃fidelity finite element model of bolt preload in this paper provides an important method for further accurate analysis of the bolt mechanics mechanism.